Dean’s Fluorosis Index: an Assessment of Examiner - Jayanth V. Kumar, DDS, MPH; Philip A. Swango, DDS, MPH; Pandy N. Opima, DDS, MPH; (Blackwell Synergy, 2000)
This report describes the interexaminer reliability achieved using Dean’s Index in a study of dental fluorosis, and shows the effect on kappa values of assigning different weights to the various components of Dean’s Index